Nilai Pedagogik Dalam Falsafah Kehidupan Masyarakat Adat Cireundeu - Ni Putu Laksmi Resti Putri; Tatang Muhtar; Yusuf Tri Herlambang (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2022)
This study aims to describe the pedagogical values in the philosophy of life of the Cireundeu Indigenous People that can be applied by teachers in classroom learning. This study uses a qualitative descriptive approach with the type of case study research. This research was conducted in the Cireundeu Traditional Village, Cimahi, West Java. The results of this study indicate that there are 3 pedagogical values from the life philosophy of the Cireundeu Indigenous Peoples that can be adopted by teachers, namely; education that follows the times, environmental education, and entrepreneurship education. Teachers are expected to be able to use these values as cultural pedagogical guidelines in the midst of the progress of the times.